2021
DOI: 10.35842/formil.v6i1.343
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko Penyakit Tidak Menular (PTM) pada Remaja: Studi Kasus pada SMA Negeri dan Swasta di Kota Yogyakarta

Abstract: Penyakit Tidak Menular (PTM) pada remaja dipicu oleh pola hidup yang tidak sehat, seperti mengkonsumsi makanan siap saji, kurang konsumsi sayur dan buah, minuman bersoda, kurang aktivitas fisik, pernah merokok, dan mengonsumsi alkohol. Menurut hasil survei kesehatan global berbasis sekolah, diketahui bahwa gaya hidup remaja saat ini berisiko terhadap penyakit tidak menular. Tujuan penelitian untuk mengetahui gambaran faktor risiko PTM pada remaja. Penelitian ini menggunakan metode deskriptif kuantitatif.  Juml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 7 publications
0
4
0
13
Order By: Relevance
“…34 Based on research conducted by Yuningrum (2021) explains that the lifestyle of today's youth is at risk of non-communicable diseases as indicated by the consumption of vegetables and fruit, most of which are in the wrong category. 12 Research conducted by other studies also showed an unhealthy lifestyle, such as consumption of soft drinks, smoking, alcohol, and lack of physical activity, which causes a high risk of non-communicable diseases. 35,36 The number of teenagers who rarely do physical activity and have a low level of physical activity to maintain body fitness is quite a lot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Based on research conducted by Yuningrum (2021) explains that the lifestyle of today's youth is at risk of non-communicable diseases as indicated by the consumption of vegetables and fruit, most of which are in the wrong category. 12 Research conducted by other studies also showed an unhealthy lifestyle, such as consumption of soft drinks, smoking, alcohol, and lack of physical activity, which causes a high risk of non-communicable diseases. 35,36 The number of teenagers who rarely do physical activity and have a low level of physical activity to maintain body fitness is quite a lot.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Previous studies have shown that risk factors for NCD that are at risk in adolescents are less consumption of vegetables and fruit and consumption of fast food. 12 In addition, adolescents are also prone to risky behavior that has not been routinely carried out, namely blood pressure checks, physical activity, exercise, lack of consumption of fruits and vegetables, fast food, and smoking habits. Early smoking is a risk factor for NCDs, such as hypertension, heart disease, stroke, and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Untuk sikap antara pre dan post-test seluruh peserta sama-sama memiliki sikap positif yaitu sebesar 100%. Hasil penelitian oleh Yuningrum et al (2021) pada 60 orang siswa SMA diperoleh hasil sebagian responden dalam menyantap sayur dan buah berada pada kategori buruk yaitu kurang dari lima porsi/hari yaitu sebesar 51 (85%). Mayoritas responden meminum minuman mengandung soda berada pada kategori baik atau tidak pernah sebesar 33 (55%).…”
Section: Kegiatanunclassified
“…Hasil survei kesehatan global berbasis sekolah di tahun 2015 atau Global Schoolbased Student Health Survey (GSHS) menemukan pola hidup remaja di jaman sekarang berisiko menimbulkan PTM (Nurhayati, 2020). Data tersebut mendapati adanya pola makan tidak sehat dalam sehari yuitu remaja mengokonsumsi makanan siap saji sebesar 53%, minimnya menyantap sayur dan buah (78,4%), minuman mengandung soda (28%), kurangnya aktifitas fisik (67,9%), pengalaman merokok (22,5%), dan minum alkohol (4,4%) (Yuningrum et al, 2021).…”
unclassified
See 1 more Smart Citation